Leveraging SharePoint Cloud for Modern Insurance Claim Management: A Technical Overview - Harsha Vardhan Reddy Yeddula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformation of insurance claim management through SharePoint Cloud implementation, highlighting its role in modernizing traditional processes. The article examines how SharePoint Cloud's integrated platform addresses key challenges in document management, collaboration, security, and process automation within the insurance sector. The article demonstrates significant improvements in operational efficiency, customer satisfaction, and cost reduction through cloud-based solutions. The platform's capabilities in handling complex workflows, ensuring regulatory compliance, and providing advanced analytics showcase its effectiveness in meeting the evolving demands of digital insurance operations. The article encompasses various aspects including document storage, real-time collaboration, security protocols, scalability, and AI integration, providing insights into how insurance organizations can leverage technology for competitive advantage.
Keywords: Cloud-based Infrastructure; Digital Transformation; Insurance Claims Management; SharePoint Integration; Workflow Automation